2021
DOI: 10.1055/s-0041-1740384
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Tibial Plateau Can Be Used as a Direct Anatomical Reference for the Posterior Tibial Slope in Medial Unicompartmental Knee Arthroplasty

Abstract: There has been no consensus about how to determine the individual posterior tibial slope (PTS) intraoperatively. The purpose of this study was to investigate whether the tibial plateau could be used as a reference for reproducing individual PTS during medial unicompartmental knee arthroplasty (UKA). Preoperative computed tomography (CT) data from 48 lower limbs for medial UKA were imported into a three-dimensional planning software. Digitally reconstructed radiographs were created from the CT data as the later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the operative eld of a modern mini-incision UKA, however, it is di cult to observe the entire MTP, including its posterior edge, until completion of the femoral bony preparation. Recently, using preoperative CT data in patients with medial UKA, we have suggested that we can refer the MTP to recreate the native PTS placing an arthroscopic probe in the anteroposterior (AP) direction on the medial second quarter of the MTP [25]. But, deformities of the MTP associated with OA progression, including cartilage remnants and cartilaginous osteophyte formation, may make it di cult to use the MTP itself as an anatomical reference.…”
Section: Introductionmentioning
confidence: 99%
“…In the operative eld of a modern mini-incision UKA, however, it is di cult to observe the entire MTP, including its posterior edge, until completion of the femoral bony preparation. Recently, using preoperative CT data in patients with medial UKA, we have suggested that we can refer the MTP to recreate the native PTS placing an arthroscopic probe in the anteroposterior (AP) direction on the medial second quarter of the MTP [25]. But, deformities of the MTP associated with OA progression, including cartilage remnants and cartilaginous osteophyte formation, may make it di cult to use the MTP itself as an anatomical reference.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using preoperative computed tomography (CT) and magnetic resonance image (MRI) data of patients who underwent medial UKA, we proposed that the MTP can be used as a direct reference to recreate the native PTS by placing a hook probe in the anteroposterior (AP) direction on the MTP [ 20 , 21 ]. This study aimed to determine the error and variance of PTS in medial UKA using a minimally invasive approach when using this new referencing method of the MTP.…”
Section: Introductionmentioning
confidence: 99%